2020
DOI: 10.1007/s11423-020-09825-x
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the structure of digital literacy competence assessed using authentic software applications

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…It appears that the DL assessed may not be independent of the technology used in the assessment, such as different digital devices, software packages, or testing platforms (cf. Reichert, Zhang et al., 2020). Moreover, technical equipment and infrastructure (e.g., internet connection) can be hurdles for remote assessment.…”
Section: Insights From the Pilot Studymentioning
confidence: 99%
“…It appears that the DL assessed may not be independent of the technology used in the assessment, such as different digital devices, software packages, or testing platforms (cf. Reichert, Zhang et al., 2020). Moreover, technical equipment and infrastructure (e.g., internet connection) can be hurdles for remote assessment.…”
Section: Insights From the Pilot Studymentioning
confidence: 99%
“…In view of this, we designed our study by planning several studies throughout the different phases to obtain enough evidence to ensure the quality of the instruments. Although the multidimensionality of the construct of DC has been identified in several studies, theoretical and empirical studies have reported contradicting results [32]. More specifically, Vuorikari et al [25] theoretically described the construct of DC in DigComp framework 2.0, but the dimensions identified have not been empirically confirmed or require further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, theoretical and empirical studies have reported contradicting results. For example, Reichert et al analysed the most commonly used digital literacy frameworks and found that empirical evidence on the use of digital applications allows for distinguishing between a general digital literacy component and four applicationspecific components (the web-based information retrieval factor, the knowledge-based information retrieval factor, the word processing factor and the digital presentation factor) [32]. Jin et al found in their custom implementation based on DigComp that DC can be considered as a general one-dimensional construct [33].…”
Section: Reference Framework For the Evaluation Of DCmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few studies capture online information use in a realistic online environment (in real time) while gathering both process and performance data and assessing development over time using pre-post-measurements. Only very few studies applied intervention designs and investigated how online media use can be promoted in educational practice (Booth, 2011; for process-related studies, Tossell et al, 2015;Gadiraju et al, 2018;Yu et al, 2018;Goldhammer & Zehner, 2017; for instruments for assessing digital media competencies and for relevant concepts, such as digital literacy, see, e.g., Reichert et al, 2020). With regard to the promotion of competent media use, only few intervention studies were found; none focused on young professionals or practical training phases.…”
Section: Current State Of Researchmentioning
confidence: 99%